THE NONMETALLIC COMPONENTS IMMERSION TEST OF THE FUEL LINE SYSTEM OF MOTOR VEHICLES WITH BIOSOLAR (B5) - Emi Yuliarita (Pusbindiklat - LIPI, 2015)
Biodiesel is a renewable alternative energy has now been used widely. The use of biodiesel in diesel fuel vehicles is the hope of anticipating the needs of increasing diesel oil. This is consistent with the national energy policy where the energy mix by 2025 is expected to use alternative energy can reach 25%. However, biodiesel has solvent properties as a good enough so that it will be able to influence the non-metallic components of the fuel line system of motor vehicles. In this study conducted immersion test against non-metallic components of the fuel line system of motor vehicles Isuzu Panter which refers to the test method SAE 1747 with the aim to see the nature of the fuel compatibility with the non-metal components. After soaking material characterization tests performed by measuring the volume and weight. The results showed that the use of 5% biodiesel in diesel fuel cause nonmetallic components undergo expansion/swelling and contracts in particular rubber, plastic, and cork. The biggest change occurred shrinkage of 71.4% on the rubber cap tank-solar, Rubber Tank Low – Solar is 28.6% and the Rubber Tank Up-Solar is 25.5% respectively in the phase after 100 hours of immersion.